# algebra

posted by .

2(w+18+W)=2(w+18−6+w+3)

• algebra -

2w + 36 + 2w = 2w + 36 - 12 + 2w + 6
0 = -6
A false statement, so ....
no solution

## Similar Questions

1. ### algebra help!!!!

Add: b^−3 ca^−1 −xc^−2 how would i do this ?
2. ### algebra

Which of the following is equivalent to the expression (t2 − t − 6)(t − 3)−1 ?
3. ### calculus

Find an equation for the surface consisting of all points P(x, y, z) equidistant from the point P(0, 1, 0) and the plane x = 3. Answer Choices: 1. y2 + z2 − 6x + 2y − 8 = 0 2. x2 + z2 + 6y − 2z − 8 = 0 3. y2 …
4. ### biology

Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?
5. ### Grade 12 Calculus

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
6. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
7. ### calculus (gr 12)

Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
8. ### Math (algebra)

Let x=2013, y=140542, z=−142555. Find [(x−y)/z + (y−z)/x + (z−x)/y]*[x/(y−z) + y/(z−x) + z/(x−y)].
9. ### linear algebra

solve using gauss jordan 10y − 4z + w = 1 x + 4y − z + w = 2 3x + 2y + z + 2w = 5 −2x − 8y + 2z − 2w = −4 x − 6y + 3z = 1
10. ### algebra or algebra1

What is the set of all values of x for which the expression x + 6 /x2 −2x−8 is not deﬁned?

More Similar Questions